Habitat suitability and distribution of Sumatran serow (Capricornis sumatraensis sumatraensis) in a Leuser ecosystem, Indonesia - SUTOPO SUTOPO; DEDE AULIA RAHMAN; IKSAN GUSTIAWAN; MISBAH SATRIA GIRI; MAFRIKHUL MUTTAQIN; MUHAMMAD SAUKI AKBAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sutopo S, Rahman DA, Gustiawan I, Giri MS, Muttaqin M, Akbar MS. 2025. Habitat suitability and distribution of Sumatran serow (Capricornis sumatraensis) in a Leuser ecosystem, Indonesia. Biodiversitas 26: 3875-3885. Determining the distribution of species and suitable habitats is a fundamental part of planning for the protection of key species. Mount Leuser National Park (MLNP), Indonesia, is habitat to the Sumatran serow (Capricornis sumatraensis sumatraensis), an endangered ungulate species. Habitat loss due to deforestation for agriculture, oil palm plantations, illegal hunting, and illegal trade in body parts are factors contributing to the increasing pressure on this species in its natural habitat. Therefore, this study aims to model the distribution of the Sumatran serow and identify priority conservation zones based on habitat suitability models. We conducted ensemble modelling implemented in the R package ‘ENMTML’ using 3 modelling techniques (MaxEnt, Random Forest, and Boosted Regression Tree) and an ensemble model. We combined 282 Sumatran serow occurrence points with 9 climate, topography, vegetation, and anthropogenic variables. The Random Forest model performed best among the three models in predicting Sumatran serow habitat, with an AUC value of 0.89 and TSS of 0.62. The Random Forest model predicts a larger area with low habitat suitability, covering 74% (610,520 ha) of the total area, with moderate habitat suitability covering 16% (131,090 ha) and high habitat suitability covering only 10% (78,139 ha) of the Sumatran serow distribution across the study area. Our model can help identify potential protection areas for this species to support its conservation. This has implications for knowledge about the current distribution and suitable habitat for Sumatran serow. Conservation efforts can be focused more effectively on core zones, particularly in Section III, Blangkejeren, and Section IV, Badar. By utilising the results of the habitat suitability model for several actions such as evaluating MLNP zoning, prioritising monitoring areas, considering corridors for connectivity, and evaluating habitat restoration programmes, conservation strategies for Sumatran serows in MLNP will be improved, and the chances of survival for Sumatran serow populations in the future can be maintained.